2019
DOI: 10.3988/jcn.2019.15.4.461
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repetitive Transcranial Magnetic Stimulation on Spasticity in Patients with Multiple Sclerosis

Abstract: Background and PurposeThis randomized controlled study examined the effect of repetitive transcranial magnetic stimulation (rTMS) on spasticity in patients with multiple sclerosis (MS).MethodsThis study included 16 patients with a history of MS and spasticity in the adductor hip muscles according to the Modified Ashworth Scale (MAS). The participants were randomized into the active group (n=10) and control group (n=6), in which active rTMS and sham rTMS were applied in 10 sessions, respectively. A physical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…White matter integrity and function is a predictor for the treatment response of rTMS for PTSD and MDD ( Barredo et al, 2019 ), and low-intensity TMS promote the survival and maturation of newborn oligodendrocytes in the adult mouse brain ( Cullen et al, 2019 ). Moreover, rTMS has also been shown to be beneficial in treating demyelinating disorders, such as Alzheimer’s disease and multiple sclerosis ( San et al, 2019 ; Chou et al, 2020 ); thus, the protective effects of myelin might be involved in the beneficial effects of rTMS.…”
Section: Introductionmentioning
confidence: 99%
“…White matter integrity and function is a predictor for the treatment response of rTMS for PTSD and MDD ( Barredo et al, 2019 ), and low-intensity TMS promote the survival and maturation of newborn oligodendrocytes in the adult mouse brain ( Cullen et al, 2019 ). Moreover, rTMS has also been shown to be beneficial in treating demyelinating disorders, such as Alzheimer’s disease and multiple sclerosis ( San et al, 2019 ; Chou et al, 2020 ); thus, the protective effects of myelin might be involved in the beneficial effects of rTMS.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five RCTs were identified as suitable for inclusion into the present review, and 23 RCTs were included in the meta-analysis (see Figure 1). 2246 For details, see Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in three studies received no pharmacological treatment except for interferon-beta, 26,30,40 while patients in five other studies were on stable pharmacological treatment. 23,24,37,39,42 The remaining 17 studies did not provide information on pharmacological treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with Xu et al (2020), the authors found rTMS did not reduce spasticity post-stroke, but the patients reported better MAS outcomes in a before-after scenario 34 . Recently, San et al (2019) showed combining rTMS with a physical therapy intervention reduces spasticity in patients with multiple sclerosis compared to physical therapy intervention alone 49 .…”
Section: Discussionmentioning
confidence: 99%